Concentration of Chlorophyll-a as the Determinant of Trophic Status in the Samsam Swamp, Kandis Sub District, Siak District, Riau Province - Silvia Karmila; Clemens Sihotang; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Samsam Swamp is a lowland swamp that receives water from the Samsam River during the rainy season. To understand the trophic status of Samsam Swamp, a present study based on the concentration of chlorophyll-a was conducted in March-April 2016. The method used was a survey method. There were four sampling stations namely Station 1, Station 2, Station 3 and Stasion 4. Samplings were conducted 3 times, once a week. Results shown that concentration of chlorophyll-a was 4.05 – 7.69 μg/L; temperature 28 – 33⁰ C, transparency 28 – 46.9 cm, water pH 4 – 5, orthophosphate 0.37 – 0.65 mg/L, nitrate 0.33 – 0.63 mg/L, dissolved oxygen 3.69 – 4.93 mg/L, free carbon dioxide 4.00 – 11.99 mg/L and depth 39 – 170 cm. Based on the concentration of chlorophyll-a, Rawa Samsam is classified as mesotrophic waters.Keywords: Lowland Swamp, Samsam Swamp, Chlorophyll-a, Trophic Status